An intelligent diagnostic system for condition monitoring of ageing glass insulators - Bashir, Nouruddeen (Praise Worthy Prize, 2011)
A strong correlation exists between leakage current (LC) and insulator surface condition in relation to contamination severity and flashover. Subsequently, systems have been developed to monitor and evaluate contamination flashover. However, few works have been reported on the relationship between LC and insulator ageing especially glass insulators and thus a system capable of diagnosing ageing transmission line glass insulators does not exist. This paper describes the design and development of an intelligent diagnostic system for ageing transmission line insulators. The system consists of hardware and computer program. The LabVIEW and MATLAB softwares were employed to develop the computer program. Results from laboratory experiments using the developed system have shown the capability and effectiveness of the system in characterizing the surface condition of aged insulators.